1984
DOI: 10.1093/ajcn/39.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Significance of postprandial blood concentrations of retinol, retinol-binding protein, and carotenoids when assessing the vitamin A status of children

Abstract: The effect of ingesting a breakfast rich in vitamin A on postprandial blood serum concentration of retinol, retinol-binding protein, and carotenoids has been investigated in children between 5 and 8 yr of age. They were divided by age in two groups (5 to 6 and 7 to 8 yr) and then randomly assigned in three groups to be studied cross-sectionally immediately before and at 2 and 4 h after the ingestion of a meal containing 337 micrograms of retinol equivalents (48% as retinol and 52% as carotenoids). The ingestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In two reported studies which included young adults (ages not given), as well as children (5-8 years old), no significant rises in total serum vitamin A levels (measured spectrophotometrically) were seen up to 4 hours after subjects consumed up to 67% of the RDA in a vitamin A-carotene mixed meal [1,2]. This method measured both retinol and retinyl esters together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two reported studies which included young adults (ages not given), as well as children (5-8 years old), no significant rises in total serum vitamin A levels (measured spectrophotometrically) were seen up to 4 hours after subjects consumed up to 67% of the RDA in a vitamin A-carotene mixed meal [1,2]. This method measured both retinol and retinyl esters together.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among 5-8-year-old children and young adults fed mixed vitamin A and carotene containing meals have shown that previous food intake has no effect on serum vitamin A levels up to 4 hours postprandially [1,2]. The authors of these studies concluded that for young subjects fasting blood for vitamin A analysis is unnecessary when assessing vitamin A status.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown stability in carotenoid and αand γ-tocopherol concentrations from the second trimester to delivery [42,43] as well as stability in dietary patterns throughout pregnancy [44,45]. The use of non-fasting plasma samples may have introduced systematic bias, but studies have shown non-significant differences in carotenoid concentrations pre-and post-meal [46,47]; the effect of fasting compared with non-fasting is less clear for plasma E vitamers due to limited literature. Findings regarding the gestational HOMA-IR were also limited by the smaller sample size, as more than half of the cohort did not provide sufficient fasting blood samples for insulin measurements.…”
Section: Discussionmentioning
confidence: 99%